The dynamic shift in therapeutic relationships through counselor self-disclosure with military client: a case study - Blackwell, Ophelia M. (Kansas State University, 2017)
This qualitative case study is designed to explore how two participants described their role with their use of counselor self-disclosure in establishing and maintaining therapeutic alliance with military clients. Utilizing purposeful and criterion-based sampling, participants for this study were counselors who worked with the military populations, had independent practices, and believed that counselor self-disclosure was beneficial in building strong therapeutic alliances with military clients. Informed by Symbolic Interactionism, the participants’ understanding of self-disclosure and its role in establishing and maintaining therapeutic alliance with military clients were explored through semi-structured, in-depth, open-ended interviews. Counselor self-disclosure (CSD) is a technique that helps to establish strong therapeutic alliances and break down barriers that may exist between the military population and their counselors. Some military members experience mental health disorders following deployments. However, these military members experience barriers when seeking treatment and they commonly terminate treatment prematurely. Findings indicate that when counselors use self-disclosure it inspires participants to open up and model their counselor’s behavior. Moreover, military clients become aware of their own symptoms that were previously invisible to them, and find ways to relate and trust the counselor. Conversely, findings also indicate that CSD can be used improperly or even when used properly could have undesired effects such as causing ruptures in the therapeutic relationship due to a lack of clients’ openness, or perceiving CSD unprofessional and an inauthentic way to elicit therapeutic alliance. This study has implications for counselor educators and practitioners to consider training about relationally-oriented cultural practices that help to prevent ruptures in therapeutic alliances with military clients. Another implication is about how CSD could be used in the preparation of students in counselor education training programs and how more inquiry could be conducted to document systematic data about the influence of CSD on therapeutic alliance. Finally, the study has implications about how CSD can facilitate support for military clients and critically understanding how CSD can aid in supporting retention or loss of treatment for military clients.
Keywords: Counselor self-dislcosure; Mililtary clients; Therapuetic relationship; Mental health; Stigma; Barriers to treatment